2016
DOI: 10.1016/j.rchipe.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Tricomicosis (tricobacteriosis) en un infante. Aspectos microbiológicos, dermatoscópicos y ultraestructurales

Abstract: TC is a rare condition that affects children, and tends to be mistaken for other diseases of the hair, such as pediculosis and mycotic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…This species has been demonstrated to cause clostridial myonecrosis in animals and humans [21] as well as severe septicaemia [22]. From the sample of patient 2, C. flavescens and C. lipophiloflavum were isolated; these bacteria are considered opportunistic pathogens of other body districts: the former causes superficial infection of the skin [23], and the latter causes vaginitis [24]. Another species isolated from patient 2 was Kocuria marina.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been demonstrated to cause clostridial myonecrosis in animals and humans [21] as well as severe septicaemia [22]. From the sample of patient 2, C. flavescens and C. lipophiloflavum were isolated; these bacteria are considered opportunistic pathogens of other body districts: the former causes superficial infection of the skin [23], and the latter causes vaginitis [24]. Another species isolated from patient 2 was Kocuria marina.…”
Section: Discussionmentioning
confidence: 99%
“…The rubra variety is the one that follows in frequency, and lastly the nigra, with very few cases reported in the literature. This is a Gram-positive, aerobic, coryneform-actinomycete bacterium, composed of bacillary and diphtheroid forms [ 16 , 17 ]. The family of these bacteria is usually part of the skin microbiota, representing around 50% [ 2 , 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, it is noteworthy that there are also cases reported in the pediatric age group, when there is still no activity of the apocrine glands, presenting on the scalp, where the number of apocrine glands is scarce or null. Therefore, we consider that the etiopathogenesis is not yet well clarified and that other mechanisms may be involved [ 17 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…A potential candidate is Conifer Green Needle Complex (CGNC), a pharmaceutical-grade complex substance from the green verdure of Pinus sylvestris and Picea abies with antibacterial, antimycotic, and antitrichomonal activity. The susceptibility of Corynebacterium xerosis and Corynebacterium flavescens to CGNC (3.5,7,15,30, 60, 125, 250, and 500 mg/mL) was evaluated using broth dilution and agar methods. The antibacterial effect of CGNC was also evaluated after exposure for 30 minutes and 1, 3, and 24 hours at concentrations of 0, 3.5, 7, 30, 125, and 500 mg/mL.…”
mentioning
confidence: 99%
“…2,10,11 Indeed, non-diphtherial corynebacteria have been implicated in central venous catheter infections in pediatric oncology patients 12 and from catheter sites in other patients. 6 Other coryneforms such as Corynebacterium flavescens have also been implicated in skin infections [13][14][15] and, in older studies, in adults with a history of intravenous drug use. 16 Antibiotic susceptibility studies have shown that corynebacteria, including C. xerosis, develop antibiotic resistance.…”
mentioning
confidence: 99%